Overview Of Readiness To Implement Electronic Medical Records At RSU Imelda Indonesia In 2023 Follows Up On Minister Of Health Regulation Number 24 Of 2022 - Maulana, Fajar; Mendrofa, Anita (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
RSU Imelda Indonesian workers plan to switch to electronic medical records, this needs to be done a readiness assessment. According to PERMENKES No.24 of 2022 states that every health service facility is required to carry out electronic medical records. Electronic medical records are the use of information technology devices for collecting, storing, managing, and accessing data stored in patient medical records in hospitals in a management system, the purpose of this study is to determine the readiness of RSU Imelda Indonesia in implementing electronic medical records. This type of research is descriptive research with a qualitative approach, the subjects in this study are medical record officers and information technology (IT) officers. The results of the study are reviewed from the Man factor, there are already officers who are responsible for processing electronic medical records as well, namely IT officers and also IT Support officers who can handle if there is a long time server system in the implementation of electronic medical records. In the Methode factor, there is no planning related to making policies and procedures regarding the application of electronic medical records. On the Money factor there is already a budget but for the budget scheme it has not yet been drawn up. In the Machine factor, facilities and infrastructure are sufficient, but it is necessary to increase the speed of the internet network in the hospital. In non-technical facilities, training and socialization have been carried out to officers related to the use of electronic medical records